2020
DOI: 10.3390/jcm9041007
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study into Burnout, Perceived Stress, Job Satisfaction, Coping Strategies, and General Health among Emergency Department Nursing Staff

Abstract: Burnout is a major problem among nurses working in emergency departments and is closely related to a high turnover of personnel, nursing errors, and patient dissatisfaction. The aims of this study were to estimate burnout, perceived stress, job satisfaction, coping and general health levels experienced by nurses working in emergency departments in Spain and to analyze the relationships between sociodemographic, occupational, and psychological variables and the occurrence of burnout syndrome among these profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 73 publications
(87 reference statements)
6
63
1
3
Order By: Relevance
“…This may be due to the high level of feminization of health professionals, which means that frontline care is mainly provided by women [ 25 ]. In addition, it may be influenced by the social role that women play with respect to caregiving [ 26 ]. Notwithstanding, the influence of gender on the phenomenon of compassion fatigue in the health care professions is not sufficiently explored and should be one of the areas for further study in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the high level of feminization of health professionals, which means that frontline care is mainly provided by women [ 25 ]. In addition, it may be influenced by the social role that women play with respect to caregiving [ 26 ]. Notwithstanding, the influence of gender on the phenomenon of compassion fatigue in the health care professions is not sufficiently explored and should be one of the areas for further study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is necessary to emphasize that it is very important to pay attention to the mental health situation of health professionals, especially in this time of pandemic [ 31 , 32 ]. Therefore, urgent and appropriate support is needed for all health workers worldwide who are working hard to control the outbreak of COVID-19 [ 33 ] and to establish early strategies that aim to prevent and treat indirect trauma [ 26 ]. This preventive approach is particularly important to avoid an increase in mental health problems among professionals at all levels [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 Active coping styles can enhance positive emotions, improve job satisfaction and increase employee retention rate. 25 26 Contrarily, individuals who use more passive coping styles tend to doubt their abilities and have worse mental health, therefore lowering their quality of life. 27 According to the transactional model of stress and coping proposed by Lazarus and Folkman in 1984, 28 an individual’s reaction to a stressful event is mediated by their subjective evaluation (ie, appraisal) of the environment and their process of coping with the event.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this increase in production in recent years may respond to the prevalence of the syndrome in nursing, as shown by Álvarez et al [ 36 ], who estimated that 43.67% of nurses have the syndrome. Although prevalence of the burnout syndrome is high in nurses in Spain [ 37 , 38 ], from around 18% to 33% [ 39 ], these percentages are similar to other countries [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 86%
“…Álvarez, Mori and Gómez [ 36 ] also found a high percentage of nursing professionals (43.67%) with burnout. Several studies in the same country have also shown high levels of prevalence of burnout in nursing professionals [ 37 , 38 ]. Thus, the prevalence of burnout in Spanish nurses would be around 18% to 33%, showing the magnitude of the problem [ 39 ].…”
Section: Introductionmentioning
confidence: 99%